Guidance And Counseling System Design With UML - Ranti Eka Putri; Virdyra Tasril; Ayu Nadia Lestari (The International Conference on Education, Social Sciences and Technology (ICESST), 2024)
This study aims to design a guidance and counseling system specifically for SMA Negeri 1 Binjai as an extension of a previous study conducted in 2023. The system is developed to enhance the efficiency and effectiveness of counseling services by facilitating better communication between students and guidance counselors. The design process utilizes Unified Modeling Language (UML), a standardized method that enables structured visual design and documentation of software systems. UML is applied through various diagrams, such as use case, and class diagrams, to ensure that the system's requirements and workflows are clearly visualized. The system design has been confirmed by the school as the end user, ensuring alignment with the specific needs of SMA Negeri 1 Binjai. With this design, it is expected that guidance and counseling services will become more responsive and supportive of students' needs in the educational environment. This research offers a practical contribution to the development of a technology-based guidance and counseling system that is relevant and can be widely applied in other high schools.